EFFECT OF ORAL AND INJECTABLE CONTRACEPTIVES ON SERUM ELECTROLYTES, WEIGHT AND BLOOD PRESSURE - HAMEED, ABDUL; MAJEED, T.; RAUF, SHAHID; ASHRAF, ASHRAF; ULLAH, NASR (Journal of Ayub Medical College Abbottabad, 2001)
Background: Since the introduction of oral and injectable contraceptives, many metabolic side effects have been reported. The use of oral contraceptive has been shown to be associated with increased level of serum electrolytes, but decrease in levels of serum electrolytes has been reported in women using injectable contraceptives. This study evaluated serum electrolytes, weight and blood pressure in women taking oral and injectable contraceptives because these changes have adverse effects on the health and economy of the subject. Methods: Serum electrolytes, weight and blood pressure were measured in 50 women taking oral contraceptive (Lofeminal) and 50 women taking injectable contraceptives (Depomedroxy progesterone acetate and Norigest). The same women served as control before starting these contraceptives. Results: There was a significant increase in serum sodium and chloride but significant decrease in serum potassium and bicarbonate level in women taking oral contraceptive. There was non-significant decrease in serum electrolytes in women taking injectable contraceptives. There was significant increase in weight and blood pressure of women taking these contraceptives